Scattered radiation dose to caregivers’ in plain radiography: a case study - Sayed, Inayatullah Shah (2019)
In radiography it is imperative to protect patients and their caregivers from adverse effects of x- radiation when they undergo diagnostic procedures. However, in certain circumstances some radiation practitioners ignore radiation protection measures that should be practiced during x-ray examinations and allow the next-in-line patient and caregiver to wait behind x-ray lead barrier inside the radiography room till the earlier patient’s examination is complete. The purpose of this case study was to measure scattered radiation dose at six different heights in the x-ray room at specific positions that might be received by patient’s caregiver. Siemens Multix Top x-ray system was used. Anthropomorphic phantom Kyoto Kagaku Phantom PBU-50 (torso) was scanned by positioning supine on examination table for anteroposterior (AP) lumbar projection. Optically stimulated luminescent (OSL) dosimeters were fixed on a wooden stick at 120, 130, 140, 150, 160 and 170 cm heights with respect to the floor. The stick was fixed in such a way to stand vertically behind the x-ray lead barrier at 2.5 meters distance from the x-ray tube. The phantom was exposed by selecting tube voltages of 68, 79 and 90 kVp at a constant tube current, 32 mAs fixing a 100 cm source to image distance (SID). Results showed that scatter radiation doses measured at different heights were different for each exposure. The highest scattered radiation dose measured was 0.0064 mGy and 0.0042 mGy at 130 cm height for 79 kVp and 90 kVp exposures, respectively. It is concluded that the measured scattered radiation doses were within the acceptable dose limits as recommended in ICRP Publication 105 for patient comforter. Nonetheless, the malpractice should not be ignored because it exposes the individual to unnecessary radiation.